Preparation method of perovskite quantum dots with efficient and stable quantum shear luminescence

By doping rare earths and transition metal ions in perovskite quantum dots and using SiO2 protective film, the problems of insufficient response and poor stability of perovskite quantum dots in ultraviolet and blue-violet light regions are solved, and efficient and stable quantum shears are achieved Cut luminescence improves the photoelectric conversion efficiency of crystalline silicon cells.

CN119286516APending Publication Date: 2025-01-10SHANGHAI XIANGUANG APPLIED MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560102.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing perovskite quantum dots have weak spectral responses in ultraviolet and blue-violet light regions, resulting in energy loss and poor stability, limiting their application in crystalline silicon solar cells.

Method used

Solution A and Solution B are prepared under the protection of inert gas, then react, add rare earths and transition metal ions doping, improve stability through SiO2 protective film, and form efficient and stable perovskite quantum dots through specific temperature and time control. .

Benefits of technology

It significantly improves the quantum yield and luminous efficiency of perovskite quantum dots, enhances its stability in complex environments, and improves the photoelectric conversion efficiency of crystalline silicon cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a preparation method of perovskite quantum dots with efficient and stable quantum shear luminescence. The method comprises the following steps: dissolving Cs2CO3 in a mixed solvent of oleic acid and 1-octadecene under the protection of inert gas, continuously stirring and heating to completely dissolve Cs2CO3 to obtain a solution A; pb (OAc) 2, transition metal chloride, YbCl3, LnCl3 and a silane coupling agent are dissolved in a methanol solution, then a mixed solvent of oleic acid, oleylamine and 1-octadecene is added, the mixture is stirred and heated to the temperature T1 and kept for t1, then the mixture is heated to the temperature T2 and kept for t2, and a solution B is obtained; and quickly adding the solution A into the solution B, reacting for t3, quickly cooling to room temperature, taking out, dispersing in toluene, adding deionized water, stirring, adding cyclohexane, precipitating, centrifuging and drying. The perovskite quantum dots obtained by the method are not only high in quantum yield, but also better in luminous efficiency and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular, relates to a method for preparing perovskite quantum dots with efficient and stable quantum shear luminescence. Background Art

[0002] Crystalline silicon solar cells have been favored by researchers due to their maximum theoretical conversion efficiency of 31% and a wider spectral response range (300-1100nm). However, due to their weak spectral response in the ultraviolet and blue-violet regions, these high-energy photons are difficult to be fully utilized, resulting in large energy losses. In recent decades, many studies have been devoted to improving the conversion efficiency of crystalline silicon cells, and using perovskite quanta for spectral conversion is an effective method.

[0003] All-inorganic perovskite quantum dots CsPbX3QD (X = Cl, Br, I) are a new type of lead halide perovskite quantum dots. They have the advantages of high absorption cross section, narrow emission line, high luminescence efficiency, emission spectrum can be greatly regulated by changing the concentration of halogen ions, and simple preparation. They have become a hot spot in the field of optoelectronic materials and photovoltaic cell devices. So far, the emission efficiency of blue-violet light materials represented by CsPbCl3QD is low, and the red light system represented by CsPbI3 is extremely unstable, which limits their practical application and becomes a key problem to be solved. Rare earth metal ions have rich transition energy levels and a wide range of luminescence wavelengths. Transition metal ions and perovskites have the most suitable bandgap width. The doping of the two can greatly improve the quantum yield.

[0004] “CsPb x Zn 1-x Cl3:Yb 3+ "Quantum Tailoring of Luminescence and Photovoltaic Applications of Nanocrystals" synthesized Yb for the first time 3+ 、Zn 2+ The more perfect crystal field environment of ion co-doped CsPbCl3PeQDs provides better conditions for quantum tailoring luminescence, making the photoluminescence quantum yield (PLQY) reach the highest 182%.

[0005] Ding et al. successfully prepared Cr by using an improved hot injection method. 3+ , Yb 3+ 、Ce 3+ Tri-doped CsPbCl3PeQDs. This material uses Cr 3+ ions to passivate CsPbCl3 defects, greatly reducing the defects, while introducing Yb 3+ , the reduction of defects makes the PLQY higher, and the total PLQY reaches up to 188%.

[0006] At present, researchers often use hot injection, room temperature antisolvent and ion exchange methods to synthesize CsPbX3 (X = Cl, Br, I) PeQDs. Among them, hot injection is a commonly used method for synthesizing PeQDs. This method uses the reaction between metal salts and organic molecules at high temperature to embed metal ions and organic molecules into the perovskite lattice to form quantum dots. Under nitrogen protection, the cesium oleate precursor solution is injected into the dissolved oleic acid (OA), oleylamine (OAm), octadecene (ODE) and PbX2 solution at a specific temperature, and then the reactants are quickly cooled to room temperature and centrifuged to obtain PeQDs precipitation. Although this method has the advantages of large preparation volume, low cost and simple operation. However, this method has the problems of difficult solute dissolution and too little element doping during the preparation process. At the same time, the prepared quantum dots have poor stability and are difficult to stably emit light in a complex environment.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The object of the present invention is to provide a method for preparing perovskite quantum dots with efficient and stable quantum shear luminescence, wherein the perovskite quantum dots obtained by the method have high quantum yield, better luminescence efficiency and better stability.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] A method for preparing perovskite quantum dots with efficient and stable quantum shear luminescence, the preparation method comprising: first preparing solution A and solution B separately, and then reacting solution A with solution B; wherein:

[0011] The process of preparing solution A is as follows: under the protection of inert gas, Cs2CO3 is dissolved in a mixed solvent of oleic acid and 1-octadecene, and the mixture is continuously stirred and heated to be completely dissolved, thereby obtaining solution A;

[0012] The process of preparing solution B is as follows: Pb(OAc)2, transition metal chloride, YbCl3, LnCl3 and silane coupling agent are dissolved in methanol solution, stirred to dissolve, then a mixed solvent of oleic acid, oleylamine and 1-octadecene is added, further stirred and heated to temperature T1, maintained for time t1, then heated to temperature T2, maintained for time t2, to obtain solution B;

[0013] The process of the reaction between solution A and solution B is as follows: solution A is quickly added to solution B, after reaction time t3, the solution is quickly cooled to room temperature, then taken out, cyclohexane is added, precipitated, centrifuged, and dried to obtain the product.

[0014] Perovskite quantum dots have the advantages of high absorption coefficient, adjustable emission position and high quantum conversion efficiency. Rare earth ions have the characteristics of wide emission wavelength range, long fluorescence lifetime and good stability due to their unique 4f-4f energy level transition. Their doping can improve the photoluminescence quantum efficiency of CsPbCl3 QD. 3+ The doped quantum dots have efficient quantum shear infrared luminescence (980nnm), which is very consistent with the peak energy conversion efficiency of crystalline silicon cells, and can greatly improve the photoelectric conversion efficiency of crystalline silicon cells. Transition metal ions have similar ionic radius and completely equivalent charge to Pb, which can further improve the photoelectric properties of quantum dots. Ln series elements can promote the absorption of ultraviolet light by perovskite quantum dots, and due to their specific energy level transitions, they provide higher energy for quantum shearing, greatly improving the quantum shearing efficiency. By co-doping transition metals, lanthanides and Yb, the perovskite quantum dots can achieve the best photoluminescence efficiency, maximizing the photoelectric conversion efficiency of crystalline silicon cells.

[0015] At the same time, in the preparation process of the present invention, methanol is used to dissolve it, so that it can be better dissolved and doped in the perovskite. At the same time, the added silane coupling agent is coated on the surface of the perovskite quantum dots as a ligand to form a layer of SiO2 protective film, which better protects the structure of the perovskite quantum dots, not only making the prepared perovskite quantum dots have better luminous efficiency, but also better stability.

[0016] Furthermore, during the preparation of solution A, the mass volume ratio of Cs2CO3 to the mixed solvent is (0.2-0.8) g: (6-16) mL.

[0017] Furthermore, the volume ratio of oleic acid to 1-octadecene in the mixed solvent is (1-2):(2-6).

[0018] Furthermore, during the preparation of solution A, the heating is performed to 180°C.

[0019] Furthermore, during the preparation of solution B, temperature T1 is 100-160°C, preferably 120°C; time t1 is 10-90 min, preferably 60 min; temperature T2 is 180-280°C, preferably 250°C; time t2 is 0-30 min, preferably 10 min.

[0020] Furthermore, in the preparation process of solution B, the usage ratio of Pb(OAc)2, transition metal chloride, YbCl3, LnCl3 and silane coupling agent is (0.1g~1.5g):(0.005g~0.05g):(0.3g~1.5g):(0.1mL~0.5mL).

[0021] Furthermore, the transition metal chloride includes ZnCl2, MnCl2, NiCl2, CrCl3 or CuCl2; the LnCl3 includes CeCl3, ErCl3, EuCl3, TmCl3, DyCl3, TbCl3 or SmCl3.

[0022] Furthermore, the silane coupling agent includes aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltrimethoxysilane, vinylethoxysilane, methyltriethoxysilane or octyltrimethoxysilane.

[0023] Furthermore, during the preparation of solution B, the volume ratio of the methanol solution to the mixed solvent is (10 mL-40 mL): (90 mL-150 mL), wherein the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent is 1:1:2.

[0024] Furthermore, during the reaction of solution A and solution B, the volume ratio of solution A to solution B is 1:(5-160).

[0025] Furthermore, during the reaction of solution A and solution B, the reaction time t3 is 10 to 300 s, preferably 10 s.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] The perovskite quantum dots obtained by the method of the present invention have high quantum yield and not only better luminous efficiency but also better stability. DETAILED DESCRIPTION

[0028] The following are specific embodiments of the present invention, and the embodiments are intended to further describe the present invention rather than to limit the present invention.

[0029] Example 1

[0030] (1) Under the protection of inert gas, 0.4 g of Cs2CO3 was dissolved in 12 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:6), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0031] (2) 0.8 g of Pb(OAc)2, 0.04 g of MnCl2, 0.8 g of YbCl3, 0.5 g of CeCl3 and 0.1 mL of aminopropyltriethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve it quickly, and then 110 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, and further stirred and heated to a temperature of 140°C (T1), maintained for 60 min (t1), and then heated to a temperature of 230°C (T2), maintained for 15 min (t2), to obtain solution B;

[0032] (3) 1 mL of solution A was quickly added to 5 mL of solution B. After a reaction time of 60 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Cyclohexane was then added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0033] Example 2

[0034] (1) Under the protection of inert gas, 0.2 g of Cs2CO3 was dissolved in 6 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:2), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0035] (2) 0.1 g of Pb(OAc)2, 0.005 g of MnCl2, 0.3 g of YbCl3, 0.3 g of CeCl3 and 0.1 mL of aminopropyltrimethoxysilane were dissolved in 40 mL of methanol solution, stirred for 10 min to dissolve rapidly, then 150 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, further stirred and heated to a temperature of 120°C (T1), maintained for 60 min (t1), then heated to a temperature of 250°C (T2), maintained for 10 min (t2), to obtain solution B;

[0036] (3) 1 mL of solution A was quickly added to 160 mL of solution B. After a reaction time of 10 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Then cyclohexane was added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0037] Example 3

[0038] (1) Under the protection of inert gas, 0.8 g of Cs2CO3 was dissolved in 16 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:3), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0039] (2) 1.5 g of Pb(OAc)2, 0.05 g of CrCl3, 1.5 g of YbCl3, 1.5 g of ErCl3 and 0.5 mL of aminopropyltriethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve them quickly, and then 120 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, and further stirred and heated to a temperature of 100°C (T1), maintained for 90 min (t1), and then heated to a temperature of 180°C (T2), maintained for 30 min (t2), to obtain solution B;

[0040] (3) 1 mL of solution A was quickly added to 10 mL of solution B. After a reaction time of 300 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Then cyclohexane was added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0041] Example 4

[0042] (1) Under the protection of inert gas, 0.4 g of Cs2CO3 was dissolved in 10 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 2:5), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0043] (2) 0.8 g of Pb(OAc)2, 0.04 g of CuCl2, 0.8 g of YbCl3, 0.5 g of ErCl3 and 0.1 mL of aminopropyltriethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve it quickly, and then 100 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, and further stirred and heated to a temperature of 160°C (T1), maintained for 10 min (t1), and then heated to a temperature of 280°C (T2) to obtain a solution B;

[0044] (3) 1 mL of solution A was quickly added to 20 mL of solution B. After a reaction time of 90 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Then cyclohexane was added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0045] Example 5

[0046] (1) Under the protection of inert gas, 0.4 g of Cs2CO3 was dissolved in 14 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:4), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0047] (2) 0.8 g of Pb(OAc)2, 0.04 g of NiCl2, 0.8 g of YbCl3, 0.5 g of EuCl3 and 0.1 mL of aminopropyltrimethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve them quickly, and then 90 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, and the mixture was further stirred and heated to a temperature of 150°C (T1), maintained for 30 min (t1), and then heated to a temperature of 200°C (T2), maintained for 20 min (t2), to obtain solution B;

[0048] (3) 1 mL of solution A was quickly added to 100 mL of solution B. After a reaction time of 90 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Then cyclohexane was added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0049] Example 6

[0050] (1) Under the protection of inert gas, 0.3 g of Cs2CO3 was dissolved in 8 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:3), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0051] (2) 0.8 g of Pb(OAc)2, 0.04 g of CrCl3, 0.8 g of YbCl3, 0.5 g of TbCl3 and 0.1 mL of aminopropyltrimethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve quickly, then 130 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, further stirred and heated to a temperature of 110°C (T1), maintained for 80 min (t1), then heated to a temperature of 250°C (T2), maintained for 25 min (t2), to obtain solution B;

[0052] (3) 1 mL of solution A was quickly added to 80 mL of solution B. After a reaction time of 120 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Cyclohexane was then added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0053] Example 7

[0054] (1) Under the protection of inert gas, 0.4 g of Cs2CO3 was dissolved in 12 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:6), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0055] (2) 0.8 g of Pb(OAc)2, 0.04 g of ZnCl2, 0.8 g of YbCl3, 0.5 g of TmCl3 and 0.1 mL of aminopropyltrimethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve rapidly, then 125 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, further stirred and heated to a temperature of 145°C (T1), maintained for 50 min (t1), then heated to a temperature of 220°C (T2), maintained for 20 min (t2), to obtain solution B;

[0056] (3) 1 mL of solution A was quickly added to 120 mL of solution B. After a reaction time of 200 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Then cyclohexane was added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0057] Example 8

[0058] (1) Under the protection of inert gas, 0.4 g of Cs2CO3 was dissolved in 12 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:6), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0059] (2) 0.8 g of Pb(OAc)2, 0.04 g of MnCl2, 0.8 g of YbCl3, 0.5 g of DyCl3 and 0.1 mL of aminopropyltrimethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve quickly, then 105 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, further stirred and heated to a temperature of 135°C (T1), maintained for 55 min (t1), and then heated to a temperature of 260°C (T2), maintained for 12 min (t2), to obtain solution B;

[0060] (3) 1 mL of solution A was quickly added to 60 mL of solution B. After a reaction time of 180 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Then cyclohexane was added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0061] Example 9

[0062] (1) Under the protection of inert gas, 0.4 g of Cs2CO3 was dissolved in 12 mL of a mixed solvent of oleic acid and 1-octadecene (the volume ratio of oleic acid to 1-octadecene in the mixed solvent was 1:6), and the mixture was stirred continuously and heated to 180°C to completely dissolve the mixture, thereby obtaining solution A;

[0063] (2) 0.8 g of Pb(OAc)2, 0.04 g of MnCl2, 0.8 g of YbCl3, 0.5 g of SmCl3 and 0.1 mL of aminopropyltrimethoxysilane were dissolved in 10 mL of methanol solution, stirred for 10 min to dissolve rapidly, then 110 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2) was added, further stirred and heated to a temperature of 112°C (T1), maintained for 45 min (t1), then heated to a temperature of 200°C (T2), maintained for 20 min (t2), to obtain solution B;

[0064] (3) 1 mL of solution A was quickly added to 100 mL of solution B. After a reaction time of 240 s (t3), the solution was placed in ice water and quickly cooled to room temperature. Deionized water was added and stirred thoroughly. Cyclohexane was then added to precipitate the solution. The solution was placed in a centrifuge and centrifuged for 10 min before being taken out and dried under vacuum to obtain perovskite quantum dots.

[0065] Comparative Example 1

[0066] This comparative example is the same as Example 1, except that methanol is not added in step (2). The specific steps are as follows:

[0067] 0.8 g of Pb(OAc)2, 0.04 g of MnCl2, 0.8 g of YbCl3, 0.5 g of CeCl3 and 0.1 mL of aminopropyltriethoxysilane were added to 110 mL of a mixed solvent of oleic acid, oleylamine and 1-octadecene (the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent was 1:1:2), stirred and heated to a temperature of 140°C (T1), maintained for 60 min (t1), and then heated to a temperature of 230°C (T2), maintained for 15 min (t2), to obtain solution B.

[0068] Comparative Example 2

[0069] This comparative example is the same as Example 1, except that YbCl3 is not added in step (2).

[0070] Comparative Example 3

[0071] This comparative example is the same as Example 1, except that the heating temperature in step (1) is 170°C.

[0072] Comparative Example 4

[0073] This comparative example is the same as Example 1, except that aminopropyltriethoxysilane is not added in step (2).

[0074] Test Example 1

[0075] This test example tests the quantum yield of the perovskite quantum dots prepared in each embodiment and comparative example. After the perovskite quantum dot sample is placed in a constant environment with a humidity of 40% and a temperature of 25° C. for 48 hours, its quantum yield is tested.

[0076] Detection method: A Hitachi F-4600 fluorescence spectrometer equipped with a 150W xenon lamp was used to collect visible luminescence spectra, and an Edinburgh FLS1000 fluorescence spectrometer was used to measure infrared luminescence spectra.

[0077] The test results are shown in Table 1:

[0078] Table 1

[0079]

[0080]

[0081] It can be seen from the results in Table 1 that the perovskite quantum dots prepared by the method of the present invention not only have high quantum yield but also have good stability.

Claims

1. A method for preparing perovskite quantum dots with efficient and stable quantum shear luminescence, characterized in that: The preparation method is as follows: firstly, solution A and solution B are prepared separately, and then solution A and solution B are reacted; wherein: The process of preparing solution A is as follows: under the protection of inert gas, Cs2CO3 is dissolved in a mixed solvent of oleic acid and 1-octadecene, and the mixture is continuously stirred and heated to be completely dissolved, thereby obtaining solution A; The process of preparing solution B is as follows: Pb(OAc)2, transition metal chloride, YbCl3, LnCl3 and silane coupling agent are dissolved in methanol solution, stirred to dissolve, then a mixed solvent of oleic acid, oleylamine and 1-octadecene is added, further stirred and heated to temperature T1, maintained for time t1, then heated to temperature T2, maintained for time t2, to obtain solution B; The process of the reaction between solution A and solution B is as follows: solution A is quickly added to solution B, after reaction time t3, the temperature is quickly cooled to room temperature, the solution is taken out and dispersed in toluene, deionized water is added and stirred thoroughly, and then cyclohexane is added, precipitated, centrifuged, and dried to obtain the product.

2. The preparation method according to claim 1, characterized in that: During the preparation of solution A, the mass volume ratio of Cs2CO3 to the mixed solvent is (0.2-0.8) g: (6-16) mL.

3. The preparation method according to claim 2, characterized in that: The volume ratio of oleic acid to 1-octadecene in the mixed solvent is (1-2): (2-6).

4. The preparation method according to claim 3, characterized in that: During the preparation of solution A, the heating is performed to 180°C.

5. The preparation method according to claim 1, characterized in that: During the preparation of solution B, temperature T1 is 100-160°C, preferably 120°C; time t1 is 10-90 min, preferably 60 min; temperature T2 is 180-280°C, preferably 250°C; time t2 is 0-30 min, preferably 10 min.

6. The preparation method according to claim 1, characterized in that: During the preparation of solution B, the usage ratio of Pb(OAc)2, transition metal chloride, YbCl3, LnCl3 and silane coupling agent is (0.1g~1.5g):(0.005g~0.05g):(0.3g~1.5g):(0.3g~1.5g):(0.1mL~0.5mL).

7. The preparation method according to claim 6, characterized in that: The transition metal chloride includes ZnCl2, MnCl2, NiCl2, CrCl3 or CuCl2; the LnCl3 includes CeCl3, ErCl3, EuCl3, TmCl3, DyCl3, TbCl3 or SmCl3.

8. The preparation method according to claim 1, characterized in that: During the preparation of solution B, the volume ratio of the methanol solution to the mixed solvent is (10 mL-40 mL): (90 mL-150 mL), wherein the volume ratio of oleic acid, oleylamine and 1-octadecene in the mixed solvent is 1:1:

2.

9. The preparation method according to claim 1, characterized in that: During the reaction of solution A and solution B, the volume ratio of solution A to solution B is 1:(5-160).

10. The preparation method according to claim 9, characterized in that: During the reaction of solution A and solution B, the reaction time t3 is 10 to 300 s, preferably 10 s.